KOLABORASI PERUSAHAAN MULTINASIONAL DAN AKTOR DOMESTIK DALAM PEMBANGUNAN SOSIAL DI NEGARA BERKEMBANG (Studi Kasus : Kiprah Toyota Motor Corporation di Indonesia) - Ummi Nurhidayah (HI 16 UMY 062, 2016)
*62 This research talk about the implementation of Corporate Social Responsibility by Toyota Motor Corporation as one of a Multinational Corporations that had expanded their activities in Indonesia, the corporate contribution activities Toyota reference of the principle of Social Contribution Toyota Global and apply some field top priority program namely, Environment, Education, Community Development and Traffict Safety. The implementation of Toyota’s CSR is in coherence with the commitment Toyota to apply triple bottom line, that sustainability company was not just about maximize of products (profit) but also to be unconcerned with the community (people) and also the environment (planet). The Toyota’s CSR activity program exercised sustainable, but there is also the other support programs. to maximize the implementation of social development in Indonesia, then Toyota synergy with domestic actors in Indonesia in implementing Corporate Social Responsibility. Keyword: Multinational Corporation, Social Development, Concept Corporate Social Responsibility, Toyota Motor Corporation, Sustainable Development